2006
DOI: 10.1111/j.1600-0722.2006.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recall assignment decisions by general dental practitioners performing routine oral examinations

Abstract: The aim of this study was to explore the decision-making behavior of general dental practitioners (GDPs) in performing routine oral examinations (ROEs). Change over time was studied by comparing data from a cohort sample of participants in two surveys in 2000 and 2005. A written questionnaire was sent to 809 dentists (509 responses were obtained) and 475 (61%) were used for analysis. Of the respondents, 347 also participated in the survey in 2000. The mean number of diagnostic ROE items per ROE was 6.9 (standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
(24 reference statements)
0
16
0
1
Order By: Relevance
“…Based on previous research, 10,23 GDPs attitude towards periodontal screening showed to be a salient determinant of individualised assessment and assignment of variable recalls. In an elderly population (65% of the patients were older than 35 years of age), the risk of developing a periodontal condition is increased.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on previous research, 10,23 GDPs attitude towards periodontal screening showed to be a salient determinant of individualised assessment and assignment of variable recalls. In an elderly population (65% of the patients were older than 35 years of age), the risk of developing a periodontal condition is increased.…”
Section: Discussionmentioning
confidence: 97%
“…This is in contrast with previous research (self-reported recall adherence in questionnaire survey) suggested a strong correlation between 'positive attitude to screening periodontal disease' and variable assigned recall intervals. 10 An explanation could be that this performance from about 70 percent of the GDPs (who stated to assign individual recall periods) is probably more driven by non-clinical factors like reimbursement and financial patient preferences than by individual oral health status. Applying more than one recall period (6 and 12 months), due above-mentioned reasons, does not necessarily mean risk-based flexible recall interval assignment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…General dental practitioners (GDPs) still assign standardised recall periods for all regular attendees. 9,10 Fuelled by quality of care aspects, GDPs are being confronted with new patient-tailored surveillance approaches. They have not been trained to screen systematically high-and lowrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 Traditionally, biannual recall has been the norm; now, more and more clinicians are undertaking an individualized risk-based recall strategy. 8,9,[12][13][14][15][16][17][18][19][20][21][22][23] One of the major aspects of recall is patient education on preventive strategies. Dietary counseling, oral hygiene instructions, and encouragement to use luoride toothpaste are important for caries control, 24,25 while smoking cessation counseling can help prevent periodontal disease and oral cancer.…”
mentioning
confidence: 99%